2011
DOI: 10.1016/j.yfrne.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor signaling in the developing neuroendocrine hypothalamus

Abstract: Fibroblast growth factor (FGF) signaling is pivotal to the formation of numerous central regions. Increasing evidence suggests FGF signaling also directs the development of the neuroendocrine hypothalamus, a collection of neuroendocrine neurons originating primarily within the nose and the ventricular zone of the diencephalon. This review outlines evidence for a role of FGF signaling in the prenatal and postnatal development of several hypothalamic neuroendocrine systems. The emphasis is placed on the nasally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 152 publications
1
40
0
Order By: Relevance
“…+ collar progenitors Emerging studies from a number of vertebrates suggest that FGF signalling plays a pivotal role in development of the neuroendocrine hypothalamus and the pituitary gland, and raise the notion that FGFs might govern the development of the infundibulum itself, potentially via effects on proliferation (for a review, see Tsai et al, 2011). Our studies suggest a mechanism for FGF function in infundibular growth, showing that FGF signalling is necessary for the proliferation of collar cells.…”
Section: Fgf Signalling Governs Proliferating Sox3mentioning
confidence: 55%
See 2 more Smart Citations
“…+ collar progenitors Emerging studies from a number of vertebrates suggest that FGF signalling plays a pivotal role in development of the neuroendocrine hypothalamus and the pituitary gland, and raise the notion that FGFs might govern the development of the infundibulum itself, potentially via effects on proliferation (for a review, see Tsai et al, 2011). Our studies suggest a mechanism for FGF function in infundibular growth, showing that FGF signalling is necessary for the proliferation of collar cells.…”
Section: Fgf Signalling Governs Proliferating Sox3mentioning
confidence: 55%
“…In all vertebrates examined, FGFs are expressed within both fpderived cells of the ventral hypothalamic midline (Manning et al, 2006) and the forming infundibulum (Tannahill et al, 1992;Ohuchi et al, 2000;Herzog et al, 2004;Theil et al, 2008;Tsai et al, 2011), where they may play multiple roles in the neuroendocrine hypothalamus. FGFs act as spatial and proliferative cues for progenitors within Rathke's pouch, which is the precursor of the anterior pituitary (Ericson et al, 1998;Norlin et al, 2000;Zhu et al, 2007), and additionally promote diverse aspects of specification of neuroendocrine neurons (Tsai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have elucidated important roles for Shh, BMP, Wnt, FGF and Nodal signaling in proper patterning of the posterior hypothalamus and the development of the hypothalamic progenitors Kapsimali et al, 2004;Lee et al, 2006;Manning et al, 2006;Mathieu et al, 2002;Ohyama et al, 2008;Pearson et al, 2011;Tsai et al, 2011;Wang et al, 2012). However, downstream factors that contribute to posterior hypothalamic neuronal specification are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that fibroblast growth factor (FGF) signaling is critical to the formation of a functional GnRH system in humans [5,6] and rodents [7]. An interesting convergence between humans and rodents is the dependence of both models on Fgf receptor 1 (Fgfr1) and Fgf8 to support GnRH neuronal development [8][9][10].…”
Section: Introductionmentioning
confidence: 99%